Information System for Product Data Collection Using Barcode System on Android-based Devices at My Kids Store Medan - Liza Fitriana; Shiva Awallu Nissa; D David (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Data collection is the most important thing in selling goods. Accuracy and speed in the process of storing and searching data are very influential in determining company profits. This research provides an alternative in implementing the data collection process using barcodes and implemented on Android-based mobile devices. It is hoped that this research will provide results in accordance with the objectives, which are to facilitate and accelerate users in processing data in order to produce accurate and fast information.